1999
DOI: 10.1096/fasebj.13.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide produced during γ‐glutamyl transpeptidase activity is involved in prevention of apoptosis and maintainance of proliferation in U937 cells

Abstract: It has been reported in several cell lines that exposure to low levels of reactive oxygen species can exert a stimulatory effect on their proliferation. We have previously shown that mild oxidative conditions can also counteract apoptotic stimuli. A constitutive cellular production of low levels of superoxide and hydrogen peroxide originates from various sources; among these, gamma-glutamyl transpeptidase (GGT), the plasma membrane-bound activity in charge of metabolizing extracellular reduced glutathione, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 46 publications
5
88
0
1
Order By: Relevance
“…Mild levels of reactive oxygen species (ROS) have been shown to induce proliferation in cancer cells [37,38]. Therefore, foods rich in antioxidant phytochemicals are important for the prevention of diseases related to oxidant stress such as heart disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mild levels of reactive oxygen species (ROS) have been shown to induce proliferation in cancer cells [37,38]. Therefore, foods rich in antioxidant phytochemicals are important for the prevention of diseases related to oxidant stress such as heart disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this is unknown. It has recently been suggested that the high levels of GGT expressed by some cell lines generates amounts of cysteinylglycine that are pro-oxidant when the cells are exposed to artificially high levels of substrate (GSH) (30). It is not known whether this effect is observed with all cells nor whether this can be translated to a lower intracellular GSH level.…”
Section: ␥-Glutamyl Transpeptidase and B Cell Viabilitymentioning
confidence: 99%
“…Furthermore, H 2 O 2 may be produced by the tumor cells themselves (17)(18)(19). This study was undertaken to address whether the decreased numbers of cytotoxic CD56 dim NK cells seen during chronic inflammation may be due to selective cell death in response to exposure to ROS produced by granulocytes.…”
mentioning
confidence: 99%